Toll-Like Receptor 2 Is Required for Optimal Control of Listeria monocytogenes Infection - Torres, David (American Society for Microbiology, 2004)
The control of Listeria monocytogenes infection depends on the rapid activation of the innate immune system, likely through Toll-like receptors (TLR), since mice deficient for the common adapter protein of TLR signaling, myeloid differentiation factor 88 (MyD88), succumb to Listeria infection. In order to test whether TLR2 is involved in the control of infections, we compared the host response in TLR2-deficient mice with that in wild-type mice. Here we show that TLR2-deficient mice are more susceptible to systemic infection by Listeria than are wild-type mice, with a reduced survival rate, increased bacterial burden in the liver, and abundant and larger hepatic microabscesses containing increased numbers of neutrophils. The production of tumor necrosis factor, interleukin-12, and nitric oxide and the expression of the costimulatory molecules CD40 and CD86, which are necessary for the control of infection, were reduced in TLR2-deficient macrophages and dendritic cells stimulated by Listeria and were almost abolished in the absence of MyD88, coincident with the high susceptibility of MyD88-deficient mice to in vivo infection. Therefore, the present data demonstrate a role for TLR2 in the control of Listeria infection, but other MyD88-dependent signals may contribute to host resistance.